PENGELOLAAN AIR BERSIH DI RS X SURABAYA - Zafira Maulidia; Mohammad Mirwan; Septin Aulidia (Yayasan Nusantara Hasana Berdikari, 2023)
To monitor, maintain, and maintain the quality of clean water in accordance with applicable regulations, optimal and effective management is needed. This research wants to look at the management of clean water which is intended to support facilities at the X Hospital in Surabaya. This study examines solutions to existing problems in clean water management. This research is intended to examine, analyze and understand the management of clean water at X Hospital Surabaya to answer the problem statement. Data were obtained from related hospitals, and various literature such as artivles and documents to access the latest data and information related to water distribution in clean water management at X Hospital Surabaya. In this study a solution to the problem of the clean water management system was obtained, namely replacing the use of chlorine in the desinfection process by using an ultraviolet lamp.